Preparation method of hydrophobic composite pigment based on chitosan modified attapulgite and hematein, hydrophobic composite pigment and application thereof

CN117462468BActive Publication Date: 2026-10-16BEIJING UNIV OF CHEM TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311577169.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2026-10-16
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

[0004]CN113234432A公开了一种以凹凸棒为载体的可逆热致变色复合颜料的制备方法,但其制备过程过于简单,染料分子直接与凹凸棒石混合,负载率不高

Benefits of technology

[0031] (1) Attapulgite has regular nanopores and abundant surface silanol groups, which have advantages such as large specific surface area, high mechanical strength, excellent thermal stability, good ion exchange capacity, and abundant surface adsorption sites, which are conducive to the adsorption of dye molecules. Attapulgite is a characteristic mineral resource in western my country, with high reserves and low cost, which reduces the preparation cost of composite pigments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117462468B_ABST
    Figure CN117462468B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of cosmetic color cosmetics and pigment preparation, and discloses a preparation method of a hydrophobic composite pigment based on chitosan modified attapulgite and hematein, wherein the attapulgite is pretreated with hydrochloric acid, then the attapulgite modified by chitosan is used to adsorb hematein to obtain a composite pigment, and finally the composite pigment is hydrophobically modified by using amino silicon oil to obtain a hydrophobic composite pigment suitable for color cosmetics. The present application has the advantages of rich raw material sources, simple and easy-to-operate steps, green environmental protection, widened application of attapulgite in the field of color cosmetics, and increased added value of attapulgite. The prepared composite pigment has excellent color and good ultraviolet stability of natural hematein, and meanwhile, the thermal stability of natural hematein is improved, so that a natural composite pigment capable of being safely and stably applied in color cosmetics is provided for consumers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite pigment preparation and color cosmetics, and particularly relates to a method for preparing a hydrophobic composite pigment based on chitosan-modified attapulgite and hematoxylin and its application in color cosmetics. Background Technology

[0002] With the improvement of economic living standards and the increasing demand for beauty, color cosmetics have become one of the fastest-growing categories in the cosmetics industry. Natural pigments are an important component of color cosmetics, and they are rich in plant sources, highly safe, and environmentally friendly and renewable. Sappanwood is an important plant dye and traditional Chinese medicine in ancient my country. Natural sappanwood pigments are rich in components such as brassinolide, possessing antibacterial and antioxidant bioactivities, and have broad application prospects in the cosmetics field. However, its stability is poor, and it is easily degraded under external factors. The main dyeing components in sappanwood heartwood include brassinolide compounds and their related derivatives, hematoxylins, proto-hematoxylins, flavonoids, chalcones, etc. Sappanwood raw materials are readily available, inexpensive, and the dyeing process is relatively simple, with high color intensity. It is one of the most important red dyes in Chinese history, widely used in dyeing clothing, paper, pigments, rouge, etc. However, as a natural pigment, the application of sappanwood in color cosmetics is limited by many problems, such as the poor stability of sappanwood pigments and their easy degradation under the influence of external factors such as ultraviolet light, acids, alkalis, and heat.

[0003] Attapulgite is a natural one-dimensional, nanoscale, hydrous magnesium aluminum silicate clay mineral with a regular nanoporous natural structure and abundant surface silanol groups. Due to its excellent thermal stability, mechanical stability, good ion exchange capacity, and abundant surface adsorption sites, it is widely used in catalyst carriers, inorganic gels, and functional coatings. Attapulgite-based composite pigments have a long history of application; as early as the ancient Mayan period, Mayan Blue, a composite pigment prepared from attapulgite and natural indigo dye, was developed. Mayan Blue exhibits extremely strong chemical stability, resisting strong acids, strong alkalis, organic solvents, oxidants, reducing agents, and biological corrosion. The mechanism of Mayan Blue's color stability lies in the unique binding mode between its pigment component, indigo, and the attapulgite carrier: indigo molecules can penetrate the channels of attapulgite and be adsorbed at different sites, mainly including the outer surface of the attapulgite crystal, grooves, and the entrances of the nanopores. The interaction between this natural pigment and the attapulgite inorganic carrier gives the pigment a rich variety of colors and excellent color stability. It can also be used as a strategy to stabilize natural pigments and solve many problems of applying natural sappanwood pigments to cosmetic pigments (such as poor color stability, easy degradation, lack of water resistance, and difficulty in makeup application).

[0004] CN113234432A discloses a method for preparing a reversible thermochromic composite pigment using attapulgite as a carrier, but its preparation process is too simple, with dye molecules directly mixed with attapulgite, resulting in a low loading rate.

[0005] CN107488363A discloses a method for loading carotenoids onto inorganic modified attapulgite, but its pretreatment process is complex and time-consuming, and pigment loading requires high pressure and demanding reaction conditions. CN113717546A discloses a method for preparing composite pigments from modified attapulgite, producing pigments with excellent lightfastness and weather resistance; however, its preparation process is overly complex and time-consuming, hindering production efficiency, and the raw materials used, such as diazonium salts, are somewhat toxic, making them unsuitable for cosmetic applications.

[0006] CN110776756A discloses a method for preparing composite pigments using modified sepiolite. The prepared composite pigments combine the color properties, thermal stability, and weather resistance of organic pigments. However, this method is only applicable to azo organic pigments and cannot be extended to the preparation of composite pigments containing natural pigments. Furthermore, azo organic pigments are not suitable for the cosmetics industry.

[0007] CN113416434A discloses a method for preparing a titanium dioxide / Maya blue-like composite pigment modified with vegetable oil and its application. The method uses a hydrothermal method to coat a layer of titanium dioxide on the surface of the Maya blue-like pigment, giving the prepared makeup pigment a sunscreen function. However, the process is complex, and the preparation of the Maya blue-like pigment requires a high temperature of over 100°C, which is not suitable for unstable natural pigments.

[0008] The process of this invention is simple and highly repeatable. The application of the prepared composite pigment in base makeup increases the added value of attapulgite and broadens the application scope of attapulgite in cosmetics and other daily chemical fields. Summary of the Invention

[0009] The purpose of this invention is to provide a method for preparing a hydrophobic composite pigment based on chitosan-modified attapulgite and hematoxylin, and the application of the hydrophobic composite pigment in the field of color cosmetics, so as to solve the problems existing in the prior art.

[0010] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0011] This invention provides a method for preparing a hydrophobic composite pigment based on chitosan-modified attapulgite and hematoxylin, comprising the following preparation steps:

[0012] (1) Attapulgite was treated with hydrochloric acid for 4-8 hours, washed with deionized water until neutral, centrifuged, dried at 105℃, pulverized and sieved to prepare acid-pretreated attapulgite.

[0013] (2) Chitosan was dissolved in 50 mL of acetic acid solution. The pretreated attapulgite obtained in step (1) was added to 50 mL of water and ultrasonically dispersed to obtain an attapulgite suspension. Chitosan acetic acid solution was added to the attapulgite suspension. The mixture was stirred at 40-80℃ for 20-30 h. The mixture was centrifuged, washed with water until neutral, dried, pulverized and sieved to prepare modified attapulgite.

[0014] (3) After the cleaned sappanwood heartwood raw material is crushed and sieved, it is mixed with 80% ethanol and then ultrasonicated. It is extracted by condensation reflux device and filtered to obtain sappanwood dye extract.

[0015] (4) The modified attapulgite obtained in step (2) and the sappanwood dye extract obtained in step (3) are stirred and mixed at 40-50℃ for 6-18h, centrifuged, and the solid precipitate after centrifugation is washed alternately with distilled water and anhydrous ethanol to remove unadsorbed dye. The precipitate is then dried, ground and sieved to prepare a composite pigment.

[0016] (5) Disperse the composite pigment obtained in step (4) in anhydrous ethanol, add amino silicone oil under stirring conditions, stir at room temperature for 1-2 hours, centrifuge, wash with anhydrous ethanol, dry, grind and sieve to obtain hydrophobic composite pigment.

[0017] Preferably, the concentration of the hydrochloric acid solution in step (1) is 0.5 to 1.5 mol / L.

[0018] Preferably, the concentration of the acetic acid solution in step (2) is 1-5% v / v;

[0019] In step (2), the ultrasonic treatment time is 10-30 min, the ultrasonic treatment temperature is 20-40℃, and the ultrasonic power is 50-150W.

[0020] In step (2), the mass ratio of raw material chitosan to acid-pretreated attapulgite is 1:5 to 10.

[0021] Preferably, in step (3), the ratio of sappanwood heartwood to ethanol is 1:25;

[0022] In step (3), the ultrasonic treatment time is 20-30 min, the ultrasonic treatment temperature is 20-40℃, and the ultrasonic power is 50-150W.

[0023] The extraction temperature in step (3) is 60℃ and the extraction time is 160-200 min.

[0024] Preferably, the ratio of modified attapulgite to hematoxylin and argyrophthalein extract used in step (4) is 1 g: 20 mL.

[0025] In step (4), the stirring temperature is 40-50℃ and the stirring time is 6-18h.

[0026] Preferably, in step (5), the ratio of composite pigment to anhydrous ethanol is 1g:10mL;

[0027] The amount of amino silicone oil used in step (5) is 1-3 mL.

[0028] Preferably, the stirring speed is 500-1000 rpm, the centrifugation speed is 3000-5000 rpm, the centrifugation time is 5-15 min, and the sieve is 100 mesh.

[0029] The present invention also provides the composite pigment prepared by the above-mentioned method for preparing hydrophobic composite pigments based on chitosan-modified attapulgite and hematoxylin and its application in base makeup pigments.

[0030] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0031] (1) Attapulgite has regular nanopores and abundant surface silanol groups, which have advantages such as large specific surface area, high mechanical strength, excellent thermal stability, good ion exchange capacity, and abundant surface adsorption sites, which are conducive to the adsorption of dye molecules. Attapulgite is a characteristic mineral resource in western my country, with high reserves and low cost, which reduces the preparation cost of composite pigments.

[0032] (2) The inorganic carrier and organic pigment of the composite pigment prepared by the present invention are both natural raw materials. The organic pigment is natural sappanwood pigment with antibacterial, anti-inflammatory and antioxidant biological activities. It has broad application prospects in the cosmetic field and is widely available. The use of attapulgite as inorganic carrier solves the problem of poor stability of sappanwood pigment, making it more stable to be used in color cosmetics and meeting consumers' demands for safety, naturalness, non-toxicity and environmental friendliness in color cosmetics.

[0033] (3) The method for preparing composite pigments provided by the present invention is simple, does not require high temperature and high pressure, is easy to operate and has high repeatability. The hydrochloric acid pretreatment expands the pore volume of attapulgite, the chitosan modification improves the adsorption capacity of attapulgite for dyes, and the amino silicone oil hydrophobic modification reduces its surface energy, improves the skin feel of the composite pigment, and enhances the cosmetic applicability of the composite pigment. Attached Figure Description

[0034] Figure 1 Comparative FTIR images of attapulgite, hematoxylin, acid-pretreated attapulgite, chitosan-modified attapulgite, composite pigment, and hydrophobic composite pigment in Example 1.

[0035] Figure 2Thermogravimetric analysis of the hematoxylin, composite pigment and hydrophobic composite pigment prepared in Example 1;

[0036] Figure 3 A comparison diagram of the contact angles of attapulgite and the hydrophobic composite pigment prepared in Example 1;

[0037] Figure 4 This is a comparison chart of the color difference ΔE values ​​of the hydrophobic composite pigments prepared in Example 1 and Comparative Example 1 in the thermal stability test;

[0038] Figure 5 The image shows a color simulation comparison of the hydrophobic composite pigments prepared in Example 1 and Comparative Example 1 during thermal stability testing.

[0039] Figure 6 This is a comparison chart of the color difference ΔE values ​​of the hydrophobic composite pigments prepared in Example 1 and Comparative Example 1 in the ultraviolet stability test;

[0040] Figure 7 The image shows a color simulation comparison of the hydrophobic composite pigments prepared in Example 1 and Comparative Example 1 in the ultraviolet stability test.

[0041] Figure 8 The image shows the vascular reaction of the chorioallantoic membrane of chicken embryos in an eye irritation test of the hydrophobic composite pigments prepared in Example 1 and Comparative Example 1. Detailed Implementation

[0042] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0043] Example 1

[0044] (1) Attapulgite was treated with 1 mol / L hydrochloric acid for 6 h, washed with deionized water until neutral, centrifuged at 4000 rpm for 10 min, dried at 105℃, and pulverized through a 100-mesh sieve to prepare acid-pretreated attapulgite.

[0045] (2) Dissolve 0.5g of chitosan in 50mL of 2% acetic acid solution, add 5g of pretreated attapulgite obtained in step (1) to 50mL of water and sonicate for 15min (power 100W, temperature 30℃) to disperse and prepare attapulgite suspension, add chitosan acetic acid solution to attapulgite suspension, stir at 60℃ and 1000rpm for 24h, centrifuge at 4000rpm for 10min, wash with water until neutral, dry at 60℃, and pulverize through a 100-mesh sieve to prepare modified attapulgite;

[0046] (3) After the cleaned sappanwood heartwood raw material is crushed and sieved, it is mixed with 80% ethanol and then sonicated. The material-liquid ratio is 1:25. The sonication is carried out for 30 minutes (power 100W, temperature 30℃). The extraction is carried out at 60℃ for 160 minutes using a reflux condenser. The sappanwood dye extract, i.e. sappanwood pigment, is obtained by filtration.

[0047] (4) Mix 1g of modified attapulgite obtained in step (2) with 20mL of sappanwood dye extract obtained in step (3) at 45℃ and 500rpm for 12h, centrifuge at 4000rpm for 10min, wash the solid precipitate after centrifugation with distilled water and anhydrous ethanol alternately to remove unadsorbed dye, dry at 45℃, grind through a 100-mesh sieve to prepare composite pigment.

[0048] (5) Disperse 4g of the composite pigment obtained in step (4) in 40mL of anhydrous ethanol, add 1mL of amino silicone oil under stirring at 500rpm, stir at room temperature at 500rpm for 1h, centrifuge at 4000rpm for 10min, wash with anhydrous ethanol, dry at 45℃, and grind through a 100-mesh sieve to obtain the hydrophobic composite pigment.

[0049] Figure 1 Comparative FTIR images of attapulgite, hematoxylin and gypsum pigment, acid-pretreated attapulgite, chitosan-modified attapulgite, composite pigments, and hydrophobic composite pigments. Figure 1 As shown, attapulgite at 1440cm -1 There is a distinct vibrational peak representing carbonate at 1440 cm⁻¹, but attapulgite pretreated with hydrochloric acid shows a peak at 1440 cm⁻¹. -1 The disappearance of the peak at 2929 cm⁻¹ indicates that acid pretreatment dissolves the carbonate cement within the pores, expanding the pore volume and improving adsorption activity. Chitosan-modified attapulgite showed peaks at 2929 cm⁻¹. -1 2857cm -1 1553cm -1 The presence of vibrational absorption peaks for -CH3, -CH2-, and NH at 1705 cm⁻¹ indicates that chitosan has been loaded onto attapulgite, thus modifying the attapulgite. Hematoxylin was observed at 1705 cm⁻¹. -1 An absorption peak for the C=O stretching vibration appears at 1358 cm⁻¹. -1 A bending vibration peak of -OH appears at 1632 cm⁻¹, while that of composite pigments and hydrophobic composite pigments is at 1632 cm⁻¹. -1 1383cm -1 and 1353cm -1 The presence of C=O and -OH vibrational peaks at all locations indicates that hematoxylin was successfully loaded onto the modified attapulgite. The hydrophobic composite pigment showed peaks at 800 cm⁻¹. -1 A Si-C tensile vibration peak appears at 2964 cm⁻¹. -1 The -CH3 stretching vibration peak appears; attapulgite shows a peak at 3399 cm⁻¹.-1 The stretching vibration peaks of -OH2 and H2O shifted to 3389 cm⁻¹. -1 This indicates that amino silicone oil binds to attapulgite via hydrogen bonds, thereby hydrophobically modifying it.

[0050] Figure 2 Thermogravimetric analysis (TGA) diagrams comparing hematoxylin, composite pigments, and hydrophobic composite pigments. (Example) Figure 2 As shown, hematoxylin begins to degrade at room temperature and rapidly loses weight at about 190℃. In contrast, the composite pigments and hydrophobic composite pigments exhibit a lower weight loss rate at 190℃ and only begin to lose weight significantly above 300℃. Their decomposition temperatures are much higher than those of hematoxylin, indicating that the thermal stability of the prepared pigments is much higher than that of hematoxylin.

[0051] Figure 3 This is a comparison diagram of the contact angles between untreated attapulgite and hydrophobic composite pigments. (Example:) Figure 3 As shown, the contact angle of the prepared hydrophobic composite pigment is above 100° and the contact angle does not decrease significantly within 30s. In contrast, the untreated attapulgite has extremely strong hydrophilicity, and the contact angle drops to zero rapidly within 10s. This indicates that the amino silicone oil hydrophobic modification used in this invention can effectively reduce the surface energy of the pigment, thereby improving the lubricity and dispersibility of the powder and the formability of the powder product.

[0052] Comparative Example 1

[0053] (1) Attapulgite was treated with 1 mol / L hydrochloric acid for 6 h, washed with deionized water until neutral, centrifuged at 4000 rpm for 10 min, dried at 105℃, and pulverized through a 100-mesh sieve to prepare acid-pretreated attapulgite.

[0054] (2) After the cleaned sappanwood heartwood raw material is crushed and sieved, it is mixed with 80% ethanol and then sonicated. The material-liquid ratio is 1:25. The sonication is carried out for 30 minutes (power 100W, temperature 30℃). The reflux device is used to extract at 60℃ for 160 minutes. The sappanwood dye extract is obtained by filtration.

[0055] (3) 1g of the pretreated attapulgite obtained in step (1) and 20mL of the sappanwood dye extract obtained in step (2) were stirred and mixed at 45℃ and 500rpm for 12h, centrifuged at 4000rpm for 10min, and the solid precipitate after centrifugation was washed alternately with distilled water and anhydrous ethanol to remove unadsorbed dye. The precipitate was dried at 45℃ and ground through a 100-mesh sieve to prepare a composite pigment.

[0056] (4) Disperse 4g of the composite pigment obtained in step (3) in 40mL of anhydrous ethanol, add 1mL of amino silicone oil under stirring at 500rpm, stir at room temperature at 500rpm for 1h, centrifuge at 4000rpm for 10min, wash with anhydrous ethanol, dry at 45℃, and grind through a 100-mesh sieve to obtain the hydrophobic composite pigment.

[0057] Test Example 1

[0058] Thermal stability test: The hydrophobic composite pigments prepared in Example 1 and Comparative Example 1 were dispersed in quartz vessels and treated at 60℃, 80℃, 100℃, and 120℃ for 6 hours before color characterization. The results are as follows: Figure 4 As shown, the color difference value ΔE of the hydrophobic composite pigment prepared by chitosan modification in Example 1 is smaller than that of the hydrophobic composite pigment prepared without chitosan modification in Comparative Example 1 under different temperature treatments. The results are consistent with... Figure 5 The color simulation image matches, indicating that the hydrophobic composite pigment prepared by the technology of this invention has better thermal stability, and its color does not show obvious changes visible to the naked eye at a high temperature of 120℃.

[0059] Test Example 2

[0060] UV stability test: The hydrophobic composite pigments prepared in Example 1 and Comparative Example 1 were dispersed in a quartz vessel and exposed to ultraviolet (UVA) light for 36 hours (UVA intensity 1.5 mW / cm²). 2 Color characterization was performed. The results are as follows: Figure 6 As shown, the color difference value ΔE of the hydrophobic composite pigment prepared by chitosan modification in Example 1 is less than that of the hydrophobic composite pigment prepared by unmodified chitosan in Comparative Example 1. The results are consistent with... Figure 7 The color simulation results match, indicating that the hydrophobic composite pigment prepared using the technology of this invention has better UV stability.

[0061] Test Example 3

[0062] In vitro oil control test: 3g (W1) of the hydrophobic composite pigment prepared in Example 1 and Comparative Example 1 was placed in a centrifuge tube, 15g of artificial sebum was added, and the mixture was allowed to stand at 37℃ for 1 hour. Then, it was centrifuged at 4000 rpm for 20 minutes. The upper oil layer was removed, and the remaining free artificial sebum was absorbed with filter paper. The weight of the sample after oil absorption was recorded as W2, and the oil absorption amount was (W2 - W1) / W1. The results are shown in Table 2. The hydrophobic composite pigment prepared in Example 1 and Comparative Example 1 can absorb approximately its own weight in sebum, and the hydrophobic composite pigment prepared in Example 1 has a better ability to absorb artificial sebum, indicating that the hydrophobic composite pigment prepared using the technology of this invention has a better in vitro oil control effect. Applying it to makeup will give the makeup oil-absorbing and sweat-absorbing effects, prolonging the makeup's longevity.

[0063] Table 1 Artificial sebum formulation

[0064] Trioleic acid glycerides 40 Palmitoleic acid 26 Wax esters 20 squalane 10 Palmitic acid 2.0 cholesterol 2.0

[0065] Table 2. Sebum Absorption Capacity (g / g)

[0066] Comparative Example 1 1.17

[0067] Test Example 4

[0068] Eye irritation test: The eye irritation of the hydrophobic composite pigments prepared in Example 1 and Comparative Example 1 was evaluated according to the ECVAM chicken embryo chorioallantoic membrane test (HET-CAM). The negative control was 300 μL of 0.9% sodium chloride solution, and the positive control was 300 μL of 0.1 mol / L sodium hydroxide solution. Fertilized chicken embryos were incubated in an incubator for 9 days at a temperature of 37±1℃ and a humidity of 65±2%. On the 10th day, the air cell position was checked with an egg candler, and an opening was made above the air cell. The eggshell above the air cell was removed using tweezers. 3 mg of the hydrophobic composite pigments prepared in Example 1 and Comparative Example 1 were weighed and applied to the vascular membrane. After 3 minutes, the test substance was quickly rinsed off with physiological saline. The changes in the blood vessels were observed under a microscope, and the degree of vascular damage was recorded and scored.

[0069] The endpoint evaluation method was adopted, and the scoring criteria and prediction model were strictly implemented according to the ECVAM chicken embryo chorioallantoic membrane test (HET-CAM) method. Vascular responses were divided into hemorrhage, coagulation, and angiogenesis. Six parallel tests were performed for each sample. The scores of the three vascular responses for each egg were summed, and the highest score among the three indicators was taken as the final S-value of that sample. The stimulus grading table is shown in Table 3. The results are shown in Table 4 and... Figure 8 As shown, the hydrophobic composite pigment prepared in Comparative Example 1 exhibited hemolysis and was mildly irritating, while the hydrophobic composite pigment prepared in Example 1 was safe and non-irritating.

[0070] Table 3 HET-CAM Stimulation Response Scoring Table

[0071] <6 Non-irritating 6≤S<12 Mild irritation 12≤S<15 moderate irritation ≥15 Severe irritation

[0072] Table 4 Eye Irritation Score

[0073] negative control 0 0 0 0 Non-irritating Positive control 18 10 15 18 Severe irritation Example 1 1 0 1 1 Non-irritating Comparative Example 1 1 1 6 6 Mild irritation

[0074] Test Example 5

[0075] The chitosan-modified attapulgite-based hematoxylin hydrophobic composite pigment prepared in Example 1 above was applied to a base makeup formulation. The human efficacy indicators of the resulting base makeup are shown in Table 5.

[0076] Table 5. Efficacy Indicators of Base Makeup

[0077] Area of ​​makeup removed 4 hours after application (%) 1.46 ΔITA° 4.64 Δb -2.67 Changes in the number of pores -110.63

[0078] The foundation prepared with hydrophobic composite pigments in this invention underwent human safety testing according to the human skin patch test method in the "Cosmetic Safety Technical Specifications." The results showed that the prepared foundation has good safety. Table 5 shows that the prepared foundation has good 4-hour wear time. After using the foundation, the ΔITA° value, representing skin whiteness, increased, indicating a significant brightening effect. The b value, representing yellowness, decreased, demonstrating the foundation's yellow-reducing effect. The number of pores decreased significantly after using the foundation, proving its excellent pore-concealing effect.

[0079] As can be seen from the above embodiments and comparative examples, the hydrophobic composite pigment prepared by chitosan-modified attapulgite in this invention is safe and non-irritating, and has better thermal stability and better UV stability in terms of color performance. The base makeup prepared by the pigment also has excellent effects in brightening, removing yellowing and concealing pores.

[0080] The reaction in this invention does not require high temperature and high pressure, and the conditions are mild. The raw materials used in each reaction are inexpensive and readily available. The operation is simple and easy to repeat. Hydrochloric acid pretreatment and chitosan modification improve the adsorption activity of attapulgite, and amino silicone oil hydrophobic modification reduces the surface energy of the pigment and improves its skin compatibility, making the heat-labile natural sappanwood pigment more stable for use in the cosmetics field.

[0081] The above embodiments are only for illustrating the technical concept and features of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a hydrophobic composite pigment based on chitosan-modified attapulgite and hematoxylin, characterized in that, The preparation steps include the following: (1) Attapulgite was treated with hydrochloric acid with a concentration of 0.5~1.5 mol / L for 4~8 h, washed with deionized water until neutral, centrifuged, dried at 105℃, pulverized and sieved to prepare acid-pretreated attapulgite; (2) Chitosan was dissolved in 50 mL of acetic acid solution. The acid-pretreated attapulgite obtained in step (1) was added to 50 mL of water and ultrasonically dispersed to obtain an attapulgite suspension. Chitosan acetic acid solution was added to the attapulgite suspension and stirred at 40~80℃ for 20~30 h. The mixture was centrifuged, washed with water until neutral, dried, pulverized and sieved to prepare modified attapulgite. The mass ratio of raw materials was chitosan: acid-pretreated attapulgite = 1:5~10. (3) After the cleaned sappanwood heartwood raw material is crushed and sieved, it is mixed with 80% ethanol at a material-to-liquid ratio of 1:25 and then sonicated. The extraction is carried out using a reflux condenser at a temperature of 60°C for 160-200 min. The sappanwood dye extract is obtained by filtration. (4) The modified attapulgite obtained in step (2) and the sappanwood dye extract obtained in step (3) are mixed at 40~50℃ for 6~18 h according to the ratio of 1g:20 mL. After centrifugation, the solid precipitate after centrifugation is washed alternately with distilled water and anhydrous ethanol to remove unadsorbed dye. The precipitate is then dried, ground and sieved to prepare a composite pigment. (5) Disperse the composite pigment obtained in step (4) in anhydrous ethanol, add amino silicone oil under stirring conditions, stir at room temperature for 1-2 h, centrifuge, wash with anhydrous ethanol, dry, grind and sieve to obtain hydrophobic composite pigment.

2. The method for preparing a hydrophobic composite pigment based on chitosan-modified attapulgite and hematoxylin according to claim 1, characterized in that, The concentration of the acetic acid solution in step (2) is 1~5% v / v; In step (2), the ultrasonic treatment time is 10~30 min, the ultrasonic treatment temperature is 20~40℃, and the ultrasonic power is 50~150 W.

3. The method for preparing a hydrophobic composite pigment based on chitosan-modified attapulgite and hematoxylin according to claim 1, characterized in that, In step (3), the ultrasonic treatment time is 20-30 min, the ultrasonic treatment temperature is 20-40℃, and the ultrasonic power is 50-150 W.

4. The method for preparing a hydrophobic composite pigment based on chitosan-modified attapulgite and hematoxylin according to claim 1, characterized in that, In step (5), the ratio of composite pigment to anhydrous ethanol is 1 g: 10 mL. The amount of amino silicone oil used in step (5) is 1~3 mL.

5. The method for preparing a hydrophobic composite pigment based on chitosan-modified attapulgite and hematoxylin according to claim 1, characterized in that, In step (1), the stirring speed is 500~1000 rpm, the centrifugation speed is 3000~5000 rpm, the centrifugation time is 5~15 min, the drying temperature is 40~80℃, and the sieve is 100 mesh.

6. A hydrophobic composite pigment, characterized in that, The hydrophobic composite pigment based on chitosan-modified attapulgite and hematoxylin is prepared according to any one of claims 1-5, wherein the hydrophobic composite pigment is heated at 120°C for 6 h or at 1.5 mW / cm². 2 The colors remained vibrant after 36 hours under UVA intensity, with no noticeable changes visible to the naked eye.

7. The application of the hydrophobic composite pigment as described in claim 6 in the preparation of color cosmetic products.

Citation Information

Patent Citations

  • Method for adsorbing stable carotenoid anti-oxidation active natural pigment by using attapulgite

    CN107488363A

  • Modified sepiolite composite pigment and preparation method thereof

    CN110776756A

  • Attapulgite-dye reversible the rmochromic composite pigment and preparation method thereof

    CN113234432A

  • Preparation method and application of vegetable oil modified titanium dioxide / Maya blue-like composite pigment

    CN113416434A

  • Method for preparing organic pigment yellow and pigment orange by modifying attapulgite

    CN113717546A